2013
DOI: 10.1038/bjc.2013.407
|View full text |Cite
|
Sign up to set email alerts
|

International validation of the EORTC QLQ-ELD14 questionnaire for assessment of health-related quality of life elderly patients with cancer

Abstract: Background:Older people represent the majority of cancer patients but their specific needs are often ignored in the development of health-related quality of life (HRQOL) instruments. The European Organisation for Research and Treatment of Cancer (EORTC) QLQ-ELD15 was developed to supplement the EORTC's core questionnaire, the QLQ-C30, for measuring HRQOL in patients aged >70 years in oncology studies.Methods:Patients (n=518) from 10 countries completed the QLQ-C30, QLQ-ELD15 and a debriefing interview. Eighty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 21 publications
0
68
0
3
Order By: Relevance
“…The original instrument 14 was self-applied by the respondents but in the population of the present study, medical and schooling characteristics were an obstacle to the self-completion of the questionnaire. We concluded that this instrument should be used in an interview format in Brazilian patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The original instrument 14 was self-applied by the respondents but in the population of the present study, medical and schooling characteristics were an obstacle to the self-completion of the questionnaire. We concluded that this instrument should be used in an interview format in Brazilian patients.…”
Section: Discussionmentioning
confidence: 94%
“…The Brazilian version of the EORTC QLQ-ELD14 14 is the result of a cross-cultural adaptation process performed in agreement with the procedures recommended by the EORTC Quality of Life Group. The process to ensure semantic and conceptual equivalence follows the Herdman universalist approach 15 , which was introduced in Brazil by Reichenheim 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Este aborda questões importantes para a QV do idoso, como independência funcional, relação com família e amigos, preocupações com o futuro, autonomia e quantidade de doença, mas só foi validado em agosto de 2013, quando o trabalho de campo do presente artigo já havia sido encerrado. 23 Ademais, o local do estudo, por ser um hospital de referência em oncologia de uma população atendida pelo SUS, pode refletir as características dessa população e não representar os idosos de todos os estratos sociais.…”
Section: Discussionunclassified
“…Progression, as well as objective response, will be defined as per the RECIST criteria for solid tumors [28] or the Cheson criteria for lymphomas [29]. HRQoL dimensions other than those targeted for the primary efficacy endpoints will similarly be assessed based on the EORTC scoring manual, and the EORTC ELD-14 module will be assessed following published guidelines [30]. For each of the HRQoL dimensions, time until definitive deterioration (TUDD) will be investigated and defined based on a recent publication [31].…”
Section: Methodsmentioning
confidence: 99%